The Ability of Composite Ni/Al-carbon based Material Toward Readsorption of Iron(II) in Aqueous Solution - Normah Normah; Neza Rahayu Palapa; Tarmizi Taher; Risfidian Mohadi; Hasja Paluta Utami; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
In this research, NiAl-LDH was synthesized using the coprecipitation method and modified with biochar and graphite to produce NiAlbiochar and NiAl-graphite composite materials. The adsorbent that has been synthesized is used for the application of adsorption of Fe(II) ions in aqueous solution. The resulting material was characterized by XRD (X-ray Diffraction) analysis, spectrophotometer FT-IR, BET analysis for determine the specific surface area and TG-DTA analysis. XRD diffractogram showed that the NiAl-Biochar and NiAl-graphite composite material had the diffraction pattern characteristic of the precursor. LDH that has been modified will have a larger surface area than the precursor. The surface area of NiAl-biochar reaches 438.942 m2/g and the surface area of NiAl-graphitereaches 21.595 m2/g. This composite material supports adsorbents with a large adsorption capacity to adsorb metals. Adsorption of Fe (II) using NiAl-Biochar and NiAl-graphite was stable for five regeneration cycles (<75.30%). The Fe(II) ion adsorption process tends to follow the Langmuir isotherm model which has a maximum capacity value (Qmax) of NiAl-Biochar composite material reaching 20 times with a value of 243.902 mg/g and the NiAl-graphite composite reaching 72.464 mg/g, so that the carbon-based composite material is considered effective. adsorbent to remove Fe(II) ion and can increase the stability of the structure for adsorption regeneration. The results of the analysis of thermodynamic parameters showed that the adsorption process was endothermic, tookplace spontaneously and the solid-liquid phase interface increased according to the increasing degree of disorder.